2005
DOI: 10.3844/ajessp.2005.119.125
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Some Bridge Pier Scour Formulae Using Field and Laboratory Data

Abstract: Estimation of maximum local scour depth at the bride pier site is necessary for the safety and economy of the designed bridge. Numerous formulae are available and almost all of these formulae were developed based on laboratory data. Validation of these formulae is necessary in order to ascertain which of the formulae will give a reasonable estimate of the local scour depth. In this study, four commonly cited formulae were selected for the validation process using both the laboratory and field data. They were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 8 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…were obtained for the model developments in this study from Landers and Mueller (1999) (384 sets of data) and Mohammed et al (2005) (14 sets of data). Table 1 summarizes…”
Section: Local Scour Problem Around a Piermentioning
confidence: 99%
See 1 more Smart Citation
“…were obtained for the model developments in this study from Landers and Mueller (1999) (384 sets of data) and Mohammed et al (2005) (14 sets of data). Table 1 summarizes…”
Section: Local Scour Problem Around a Piermentioning
confidence: 99%
“…Johnson (1995) reported that the Melville and Sutherland formula tends to over-predict d s to greater extent than any other formulae. Recently, Mohammed et al (2005) showed that the Laursen and Toch (1956) and the Colorado State University (CSU) formulae (Mohammed et al, 2005) give reasonable estimates, whilst the Melville and Sutherland (1988) and Jain and Fisher (1980) formulae over-predict pier scour based on the comparison of some bridge pier scour formulae using field and laboratory data.…”
Section: Introductionmentioning
confidence: 99%
“…Originally, this formula was presented in HEC-18 (Richardson and Davis 2001) and was recently used by Mohamed et al (2005) for comparison with other regression-based equations.…”
Section: Richardson and Davis (2001) Formulamentioning
confidence: 99%
“…In recent decades, many studies have been undertaken to predict the exact depth of local scour (for example Laursen and Toch, 1956;Shen, 1971;Hancu, 1971;Breusers et al, 1977;Melville and Sutherland, 1988;Richardson et al, 1993;Mohammed et al, 2005;Alias et al, 2008;Kumar and Sreeja, 2012;among others). Through physical laboratory tests, these studies derived the dominant parameters of local scour, such as flow velocity, water depth, pier width, pier length, and flow angle, and then proposed empirical formulae using these parameters.…”
Section: Introductionmentioning
confidence: 98%